Analysis of aeromedical retrieval coverage using elliptical isochrones: An evaluation of helicopter fleet size configurations in Scotland. Issue 3 (March 2017) - Dodds, Naomi; Emerson, Philip; Phillips, Stephanie; Green, David R.; Jansen, Jan O.
Abstract : BACKGROUND: Trauma systems in remote and rural regions often rely on helicopter emergency medical services to facilitate access to definitive care. The siting of such resources is key, but often relies on simplistic modeling of coverage, using circular isochrones. Scotland is in the process of implementing a national trauma network, and there have been calls for an expansion of aeromedical retrieval capacity. The aim of this study was to analyze population and area coverage of the current retrieval service configuration, with three aircraft, and a configuration with an additional helicopter, in the North East of Scotland, using a novel methodology. Both overall coverage and coverage by physician-staffed aircraft, with enhanced clinical capability, were analyzed. METHODS: This was a geographical analysis based on calculation of elliptical isochrones, which consider the "open-jaw" configuration of many retrieval flights. Helicopters are not always based at hospitals. We modeled coverage based on different outbound and inbound flights. Areally referenced population data were obtained from the Scottish Government. RESULTS: The current helicopter network configuration provides 94.2% population coverage and 59.0% area coverage. The addition of a fourth helicopter would marginally increase population coverage to 94.4% and area coverage to 59.1%. However, when considering only physician-manned aircraft, the current configuration provides only 71.7% population coverage and 29.4% area coverage, which would be increased to 91.1% and 51.2%, respectively, with a second aircraft. CONCLUSIONS: Scotland's current helicopter network configuration provides good population coverage for retrievals to major trauma centers, which would only be increased minimally by the addition of a fourth aircraft in the North East. The coverage provided by the single physician-staffed aircraft is more limited, however, and would be increased considerably by a second physician-staffed aircraft in the North East. Elliptical isochrones provide a useful means of modeling "open-jaw" retrieval missions and provide a more realistic estimate of coverage. LEVEL OF EVIDENCE: Epidemiological study, level IV; therapeutic study, level IV.